An Electrical Double Layer Theory for Platelet Adhesiveness and Initiation of Intravascular Thrombosis - Dawber, J. G; Roberts, J. C (Thrombosis and Haemostasis, 1968)
A theory based upon the concept of zeta potential is suggested for platelet adhesiveness. It is postulated that substances influence platelet adhesiveness by affecting the zeta potential at the platelet surface. The theory is tested by measuring the effects of various physiologically active compounds upon the streaming potential of saline solution flowing through a sintered glass membrane. The effects of the compounds on the streaming potential and hence zeta potential at the glass/liquid interface parallels their effects on platelet adhesiveness. The theory is extended to include the zeta potential of the vascular endothelium.